STRATEGI PEMENANGAN PARTAI NASDEM DALAM PEMILU 2014 DI JAWA TENGAH - Dessy Lestiani; Fitriyah .; Wiwik Widayati (Journal of Politic and Government Studies, 2014)
Thesis with the title " Winning Strategies Nasdem Party in the 2014 election in Central Java " is made to determine how political marketing strategy NasDem Party as a new party with the aim of winning the legislative elections in 2014 , especially in Central Java . The method used is a qualitative research model , the descriptive type . The primary data obtained through interviews with sources in this case the DPW board NasDem Party Central Java . Secondary data was obtained through literature and articles that are relevant to the research focus .The results of the study are in the preparation of the strategy to win the 2014 election , the Party Central Java NasDem refers to the strategic plan compiled from NasDem Party Center . The strategy includes strengthening and establishment of structures up to the formation of regions with output management NasDem Party in 35 districts / cities and 573 DPC level Party Village / Subdistrict . Institutional Strengthening of the coordination of procurement meeting , a gathering of national leaders and volunteers NasDem formation . Rekuitmen members with O250 program . Party socialization to the community with a program " NasDem Fever " . Party- Rekuitmen . Rekuitmen witnesses and TPS officers . Election preparation and implementation of the 2014 election campaign .Keyword : NasDem party, Winning Strategies